The Analysis of Strawberry Powder Content and Potential Implications as Anti-Obesity - Azzahra Nur Fadhilah; Ida Nurwati; Setyo Sri Rahardjo (Indonesian Journal of Global Health Research, 2025)
The prevalence of obesity in Indonesia has increased from 21.8% in 2018 to 23.4% in 2023. Contributing factors include an unbalanced diet, lack of physical activity, and genetic factors. One strategy for dealing with obesity is regulating diet with nutritious intake. Strawberries are rich in antioxidants and flavonoids that are beneficial for obese groups, such as improving lipid profiles and reducing oxidative stress. Its high water content makes is perishable, processing it into powder can increase shelf life without reducing its nutritional content. This article examines the nutritional content and benefits of strawberry powder in managing obesity. Method: A descriptive research design with laboratory analysis approach. The powder making process began with drying using a cabinet dryer at a temperature of ±40-600C for 16 hours, followed by grinding process using a grinder, the compound content in strawberry powder was analyzed. Analysis revealed that 100 grams of strawberry powder contained 3.18% fat, 6.43% protein, 71.67% carbohydrates, 0.57% crude fiber, 397.72 mg vitamin C, 77.63% antioxidant inhibition and 555.10 ppm anthocyanin. The drying and powdering processes didn’t significantly reduce the compound content of the strawberry. Strawberry powder demonstrated potential as an anti-obesity agent, offering benefits in improving obesity biomarkers.